Budaya Mutu dalam Pendidikan Islam: Tantangan dan Peluang - Kholil, Ahmad Agus Afwil (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to examine the application of quality culture in Islamic education at MA Al Amiriyyah Blokagung. This study collects data from interviews with madrasah heads, teachers, and students as well as direct observation of the implementation of education policies and evaluations. Data analysis was carried out qualitatively with the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that MA Al Amiriyyah has implemented a culture of quality with a focus on commitment to the quality of education, teacher competence, and quality-based evaluation. Although there have been significant efforts to maintain the quality of education through teacher development and the implementation of holistic evaluation, there are still some major challenges, such as limited facilities, time, and training for teachers. On the other hand, the support of the pesantren community and the existence of quality improvement programs provide a great opportunity to overcome these obstacles. The conclusion of this study is that the implementation of quality culture in MA Al Amiriyyah has shown positive results in improving the quality of Islamic education. However, to achieve more optimal results, madrasas need to strengthen infrastructure, provide more intensive training for teachers, and optimize synergy between madrasas, parents, and the pesantren community.